Epidermal nevus/Lichen striatus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2004)
Many skin disorders are distributed according to the Blaschko lines, namely the lines of migration of skin cells during embryogenesis. Among the more frequent childhood disorders there are epidermal nevus, which is usually present at birth and lichen striatus, a rather frequent acquired pediatric disorder. The differential diagnosis between these two conditions is important from a prognostic point of view because epidermal nevus persists essentially unchanged throughout life, whereas lichen striatus in most cases regresses within several months.